2004
DOI: 10.1002/hup.604
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine improves antisaccade task performance without affecting prosaccades

Abstract: Although there is ample evidence for a cognitive-attentional benefit of the stimulant nicotine, the source of this benefit is not as well understood. One approach is to address what aspects of performance nicotine affects at a functional systems level. It is currently debated whether the benefits produced by nicotine are the effect of enhanced higher cognitive function or reflect an overall increase in general arousal. In order to address this question, the effects of nicotine on two simple eye movement tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
6
26
0
1
Order By: Relevance
“…This study did not find any effect on healthy controls but was primarily a study of schizotypy, so it included only seven healthy participants. However, the finding here that Damphetamine reduced antisaccade errors is consistent with previous findings in healthy adults using another stimulant, nicotine (Dépatie et al 2002;Powell et al 2002;Larrison et al 2004;Rycroft et al 2006).…”
Section: Discussionsupporting
confidence: 94%
“…This study did not find any effect on healthy controls but was primarily a study of schizotypy, so it included only seven healthy participants. However, the finding here that Damphetamine reduced antisaccade errors is consistent with previous findings in healthy adults using another stimulant, nicotine (Dépatie et al 2002;Powell et al 2002;Larrison et al 2004;Rycroft et al 2006).…”
Section: Discussionsupporting
confidence: 94%
“…Nicotine has previously been shown to improve prepotent response inhibition (Della Casa et al 1998;Larrison Briand and Sereno, 2004). In our study, the strategic change that resulted in more fixations on target letters could reflect more effective inhibition of overt eye-movements towards task irrelevant items, or enhanced monitoring of the ongoing task.…”
Section: Discussionsupporting
confidence: 46%
“…Similarly intrusive anticipatory saccades that can occur during smooth pursuit eye movements have been argued to reflect a failure of inhibitory control mechanisms [Avila et al 2003]. Studies in patients with schizophrenia, who demonstrate both increased antisaccade errors and impaired smooth pursuit have found that nicotine can significantly ameliorate both of these deficits [Olincy et al, 2003;Larrison Briand and Sereno, 2004). Avila et al (2003) have reported that nicotine reduces the number of leading (or anticipatory) saccades during smooth pursuit tasks both in people with schizophrenia and in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nicotine has been shown to decrease inhibitory failures on the antisaccade task compared to placebo (Larrison, Briand, and Sereno, 2004), especially in regular smokers following a period of abstinence (Dawkins et al, 2007;Powell, Dawkins, and Davis, 2002). Similarly, amphetamine decreased inhibition errors on the antisaccade task in a group of healthy controls (Allman, 2010), and methylphenidate did the same in a sample of young adults with ADHD (Klein, Fischer, Fischer, and Hartnegg, 2002).…”
Section: Examination Of Acute Drug Effectsmentioning
confidence: 99%